P104 Orion xTask: Improving neurosurgical workflow using an electronic tasks system. (8th April 2021) - Koh, Chan Hee; Nathan, Arjun; Goacher, Edward; Fernandez-Mendez, Rocio; Owen, Nicola; Martin, Michael; Davies, Benjamin Marshall; Joannides, Alexis; Koh, Chan Hee
Abstract: Introduction: The dominant form of communication within hospitals remains the antiquated paging system. Pitfalls to pagers include: overwhelming volume of non-urgent bleeps; inability to prioritise at the point-of-bleep; no written record of communication - potentially compromising patient safety. Orion xTask, an electronic tasks system, was implemented at Cambridge neurosurgery in April 2019 to mitigate some of these pitfalls. Methods: Bleep logs, covering 2-months before and 4-months after xTask implementation with total 3181 bleeps, were obtained. xTask data for the same period (total 4195 electronic requests) was exported. Bleep response times for neurosurgery and for other specialties without xTask were collected. Questionnaires were distributed to nursing and medical staff. Results: Daily averages of 14.4 in-hours and 23.7-out-of-hours electronic requests were made. The exception to greater out-of-hours utilisation was the ward without a dedicated doctor, where requests peaked in the morning. Prescription was most commonly requested (49%), followed by clinical review (17%). There were daily averages of 13.0 in-hours and 8.3 out-of-hours bleeps. Changes in bleep volume with xTask implementation were inconsistent: Calls to ward bleeps decreased (p = 0.044), but increased to the on-call (p = 0.042). Bleep response times, and (bleeped-)job completion times were significantly quicker for neurosurgery than for other specialties (p < 0.001). Nursing and doctors' feedback was overwhelmingly positive, with agreement that xTask improves patient safety. xTask scored particularly highly on "Improves Communication", "Improves Record Keeping" and "Useful Out-of-Hours". Doctors indicated that xTask also "Helps Prioritisation" and "Facilitates Educational Opportunities". Conclusion: The feedback and pattern-of-use indicates that Orion xTask successfully mitigates some of the pitfalls of pagers, thereby improving patient safety.